Long-Term Dynamics Of Tropical Rainforest Land Cover In Lawe Gurah Resort, Gunung Leuser National Park, 1990–2024 - Nurhasanah; Halus Satriawan; Cut Azizah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Long-term land-cover records are essential for evaluating ecological change at the operational scale of protected-area management. This study quantified land-cover dynamics in Lawe Gurah Resort, Gunung Leuser National Park, using nine harmonized GIS layers for 1990, 1996, 2000, 2006, 2011, 2016, 2021, 2023, and 2024. Area, percentage, absolute change, and mean annual change were calculated for each mapped class. Primary dryland forest declined from 51,349.34 ha in 1990 to 37,944.04 ha in 2024, a reduction of 13,405.30 ha (26.11%; 394.27 ha yr−1). Secondary dryland forest increased from 980.99 to 12,281.11 ha, while combined primary and secondary forest decreased more moderately from 52,330.33 to 50,225.15 ha (4.02%). Forest share therefore fell from 97.11% to 93.25%. Shrubland doubled to 1,654.67 ha, and mixed dryland agriculture reached 1,531.54 ha after first appearing in 2011. The results show a substantial shift in forest composition alongside a smaller net contraction of total forest. Management should prioritize recurrent mapping, field verification, and targeted surveillance of areas where secondary forest, shrubland, and mixed agriculture have expanded.